The US-EC confrontation in the GATT from an EC perspective - Eckart Guth; Tonia Pankopf (Intereconomics, 1993)
Negotiations on agriculture have for a long time been the centre piece and the stumbling block of the Uruguay Round. While the EC has had to bear the brunt of public criticism, the US has clearly contributed its fair share to bringing about the present unsatisfactory state of affairs. This article focuses on the latter's role in international agricultural trade.
Keywords: 330; Uruguay Round